Spatiotemporal variability of polybrominated diphenyl ether concentration in atmospheric fine particles in Shenzhen, China. (July 2018) - Peng, Jinling; Wu, Dongting; Jiang, Yousheng; Zhang, Jianqing; Lin, Xiaoshi; Lu, Shaoyou; Han, Pengpeng; Zhou, Jian; Li, Shengnong; Lei, Yixiong; Chen, Jinsong
Abstract: Polybrominated diphenyl ethers (PBDEs) are widely used as flame retardants for various products and have become ubiquitous pollutants in environmental media. However, little is known about PBDE levels in Shenzhen, a manufacturing center of electronic products. This study aimed to investigate spatiotemporal variability of PBDE concentration in atmospheric fine particles (PM2.5 ) and to estimate the daily inhalation exposure doses for local residents in Shenzhen, China. A total of 36 samples were collected and 8 PBDE compounds (BDE-28, 47, 99, 100, 153, 154, 183 and 209) were analyzed by isotope dilution high-resolution gas chromatograph/high-resolution mass spectrometer (HRGC/HRMS). Mean concentrations of Σ8 PBDEs and BDE-209 in PM2.5 in Shenzhen were 33.47 pg/m 3 and 24.75 pg/m 3, respectively, which were lower than those for other reported cities from China. The mean concentration of Σ8 PBDEs was higher in the winter + spring than that in summer + autumn, and both concentrations of BDE-28 and BDE-47 in PM2.5 were significantly higher in winter + spring than those in summer + autumn. Among the 8 congeners, BDE-209 was predominant, accounting for 73.9% of the Σ8 PBDEs concentrations. Traffic area, industrial area, residential area and discharge of electronic industries had significant positive influences on PBDE concentrations in PM2.5 . Both vegetation area and water area were significantly negatively correlated with PBDE levels in PM2.5. Significantly negative correlation was also found between PBDE concentrations in PM2.5 and the relative humidity. The ranking of estimated inhalation exposure doses of PBDEs via PM2.5 inhalation were toddlers (1.74 pg/kg b.w./day) > children (1.33 pg/kg b.w./day) > adults (1.26 pg/kg b.w./day) > teenagers (0.64 pg/kg b.w./day), and toddlers had a highest risk to expose to PBDEs by PM2.5 . To our knowledge, the present study is the first to reveal the spatiotemporal variability of PBDEs in PM2.5 of Shenzhen, China. Graphical abstract: Image 1 Highlights: Spatiotemporal variability of PBDE levels in PM2.5 was first showed in Shenzhen, a electronic manufacturing center in China. The mean concentration of Σ8 PBDEs was higher in the winter and spring than that in summer and autumn. Areas of traffic, industrial, residential and electronic discharges were positively correlated with PBDE levels in PM2.5 . Areas of vegetation and water, and relative humidity had negative influence on PBDE levels in PM2.5 . Toddlers had a highest risk to expose to PBDEs via PM2.5 inhalation. Abstract : The concentrations, profiles, spatial distributions, and seasonal variations of PBDEs were first reported in atmospheric fine particles from Shenzhen, China.